Peran Sipamandar Pada Pengambilan Keputusan Anggaran Pemerintah Kabupaten Mamuju - Adelia; Putri, Redina; Yeni, Hari (CV. SINAR HOWUHOWU, 2026)
Regional financial management that is transparent, efficient, and accountable is a crucial element in achieving good governance. The Government of Mamuju Regency has implemented SIPAMANDAR (Regional Financial Management Information System) to support the processes of planning, budgeting, implementation, and financial reporting. This study aims to analyze the role of SIPAMANDAR in supporting budget decision-making and to identify the supporting and inhibiting factors in its implementation. This research employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews with regional financial management officials, budget planners, and SIPAMANDAR operators, complemented by observation and documentation studies. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that SIPAMANDAR plays an important role in providing accurate, integrated, and timely financial information, thereby supporting more rational budget decision-making. However, its implementation still faces challenges, including limitations in human resources, technological infrastructure, and inter-departmental system integration.